Quantum leaps - Bernstein, Jeremy, 1929- (Cambridge, Mass. : Belknap Press of Harvard University Press, 2009)
How-- and how pervasively-- quantum mechanics has entered the general culture is the subject of this book, an engaging, eclectic, and thought-provoking look at the curious, boundlessly fertile intersection of scientific thought and everyday life.
An introduction -- Bishops -- Quantum Buddhists -- Léon Rosenfeld -- A double slip -- A measurement -- Entanglements -- Anyway, what the #$*! do we know? -- L'Envoi.
Includes bibliographical references and index.
Keywords: Quantum theory -- Miscellanea